Real and Presumed Categories: A Formal Approach - Uriagereka, Juan (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2025)
Categorization is fundamental to any scientific pursuit, posing the question of what categories themselves amount to. Are categories absolute or mere linguistic constructs? If the latter, are they to be trusted? Otherwise, what can one use to ground categories? The present piece reminds us that one can go about this substantively or formally. Substantive, for beings with a neuro-physiological nature, boils down to how we happen to be “wired” or how our brain “works”, whatever that means. Formal ought to be grounded on some abstract system, of the sort that logic and arithmetic represent — given “the unreasonable effectiveness of mathematics”. In this context, I consider whether primitive linguistic (distinctive) features are substantive or formal. In the end, I suggest that this depends on the nature of the feature, and that in some fundamental sense there is ample space for foundational formal features, which has a variety of technical and philosophical consequences worth pursuing.